CULTURAL REPRESENTATION IN ENGLISH TEXTBOOKS USED IN INDONESIAN SCHOOLS: A CRITICAL CONTENT ANALYSIS OF SOURCE, TARGET, INTERNATIONAL, AND INTERCULTURAL DIMENSIONS - Dyoty Auliya Vilda Ghasya; Helminsyah Helminsyah; Nurul Fatehah Binti Norhazaruddin (SENSEI RESEARCH CENTER, 2025)
The English textbook is not only about the language but also brings the culture. Sometimes the culture in the textbook is only from the western countries, so the students do not know much about their own culture. This study discusses the cultural representation in English textbooks that are used in Indonesian schools. The study used a qualitative method with content analysis. The data were three English textbooks. The result shows that the culture in the textbooks is dominated by the target culture and the local culture is still small, and also the tasks only ask the students to identify the culture and not to compare it. Therefore the textbook writers should give more portion to the local culture.